Gender Dynamics in Team Communication: Analyzing Compliments Among Chinese College Athletes - Shanshan Chen,; Qian Liu,; Miaomiao Ren, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Compliments are not only common polite speech acts but also play a crucial role in social interactions, significantly impacting team cohesion and dynamics in sports. This study investigates gender differences in compliment-giving strategies among Chinese college athletes, exploring how these differences influence team communication and social cohesion. We propose three hypotheses: (1) there are distinct compliment strategies between genders; (2) these strategies differ notably in contexts such as appearance, performance, and possessions; and (3) they vary according to perceived social status within the team. To test these hypotheses, we designed a series of interviews tailored to understand the nuances of compliment usage among male and female athletes. Our findings indicate that gender plays a significant role in shaping compliment strategies, which in turn affects interpersonal relationships within teams. The differences observed are partly attributed to the traditional roles and expectations imposed by society, which are still prevalent despite the influence of Western cultural norms on modern Chinese society. This research highlights that understanding these gender-specific communication strategies is essential for coaches and sports psychologists aiming to foster a more inclusive and supportive team environment. Accepting compliments, often perceived as politeness, can be seen as a form of positive reinforcement that enhances team morale and individual self-esteem, essential factors in athletic performance.